Oral immunotherapy using boiled peanuts for treating peanut allergy: An open‐label, single‐arm trial. Issue 3 (11th January 2023) - Grzeskowiak, Luke E.; Tao, Billy; Aliakbari, Kamelya; Chegeni, Nusha; Morris, Scott; Chataway, Tim
Abstract: Background: Peanut allergy affects 1%–3% of children in Western countries. Boiling peanuts has been demonstrated to result in a hypoallergenic product that may provide a safer way of inducing desensitization in peanut‐allergic patients by first inducing tolerance to boiled peanut. We aimed to assess the efficacy and safety of oral immunotherapy (OIT) using sequential doses of boiled peanuts followed by roasted peanuts for treating peanut allergy in children. Methods: In this open‐label, phase 2, single‐arm clinical trial, children aged 6–18 years with a positive history of peanut allergy and positive peanut skin prick test ≥ 8 mm and/or peanut‐specific IgE ≥ 15 kU/L at screening underwent OIT involving sequential up‐dosing with 12‐hour boiled peanut for 12 weeks, 2‐hour boiled peanut for 20 weeks and roasted peanut for 20 weeks, to a target maintenance dose of 12 roasted peanuts daily. Primary outcome: proportion of children passing open‐label oral food challenge involving cumulative administration of 12 roasted peanuts (12 g peanuts; approximately 3000 mg peanut protein) 6–8 weeks after reaching the target maintenance dose. Secondary outcomes included treatment‐related adverse events and use of medications for treating allergy symptoms. Results: Between 1 July 2017 and 22 June 2018, 70 participants were enrolled and commenced OIT. Desensitization was successfully induced in 56 of 70 (80%) participants. Withdrawal due to treatment‐related adverse events was infrequent ( n  = 3). Treatment‐related adverse events were reported in 43 (61%) participants, corresponding to a rate of 6.58 per 1000 OIT doses. Medication use associated with treatment‐related adverse events was infrequent, with rescue epinephrine use reported by three (4%) participants (0.05 per 1000 doses). Conclusion: Oral immunotherapy using boiled followed by roasted peanuts represents a pragmatic approach that appears effective in inducing desensitization and is associated with a favourable safety profile. Abstract : Peanut‐allergic children underwent oral immunotherapy involving sequential up‐dosing with 12‐hour boiled peanut for 12 weeks, 2‐hour boiled peanut for 20 weeks and roasted peanut for 20 weeks, to a target maintenance dose of 12 roasted peanuts daily, following which they underwent a supervised oral food challenge. In this open‐label study, immunotherapy using boiled followed by roasted peanuts represents a pragmatic approach that appears effective in inducing desensitization and is associated with a favourable safety profile.